Stress responses in juvenile pacu (Piaractus mesopotamicus) submitted to repeated air exposure - DOI: 10.4025/actascianimsci.v30i1.3618 - Biller, Jaqueline Dalbello; Bendhack, Fabiano; Takahashi, Leonardo Susumu; Urbinati, Elisabeth Criscuolo (Acta Scientiarum. Animal Sciences, 2008)
Juvenis de pacu (5,2 Pacu juveniles (5.2 ± 1.5 g) were submitted to two one-minute air exposures in a 24 h interval, and sampled before the exposure (control) and 5, 15, 30 and 60 min, 24 and 48 h afterwards for whole-body cortisol, sodium, potassium and calcium ion concentrations. For the first air exposure, there was a trend of increased cortisol concentration after 15 min, whereas in the second air exposure, the cortisol concentration increased significantly within 5 min after stress was induced. Sodium ion concentration increased significantly 24 h after both air exposures. Potassium concentration presented fluctuations over the experimental period. Calcium ion concentration increased progressively from 5 to 30 min, in both air exposures. The repeated air exposures exacerbated the cortisol response, but they did not affect the recovery ability of pacu over the experimental period. Additionally, the whole-body cortisol measurement might be a reliable indicator of stress, when sampled fish are smaller and blood volumes are very low, making samples inadequate for analysis1,5 g) foram submetidos a duas exposições aéreas de um minuto, em intervalo de 24 horas, e amostrados antes da exposição (controle) e 5, 15, 30 e 60 min, 24 e 48 horas depois para análise da concentração corporal de cortisol e dos íons sódio, potássio e cálcio. Na primeira exposição, os peixes apresentaram concentrações de cortisol aumentadas a partir de 15 min, embora não diferissem estatisticamente do controle. Na segunda exposição, a concentração de cortisol aumentou significativamente aos 5 min, retornando às concentrações equivalentes às dos peixes-controle em 30 min. A concentração do íon sódio aumentou significativamente 24 horas depois das duas exposições aéreas. A concentração do íon potássio apresentou flutuações durante o experimento, enquanto a do cálcio apresentou-se reduzida aos 5 min, aumentando gradativamente até os 30 min, nas duas exposições. A repetição do fenômeno estressor exacerbou a liberação de cortisol, mas não afetou a capacidade de recuperação dos peixes. A análise do cortisol tecidual pode ser considerada um indicador confiável de estresse.